The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1149/05701.0205ecst
|View full text |Cite
|
Sign up to set email alerts
|

Stack Temperature Estimation in System Environment by Utilizing the Design of Experiments Methodology

Abstract: The behavior of the maximum temperature measured inside a SOFC stack with respect to three independent input variables (stack current, air flow and air inlet temperature) is examined by using a full factorial screening experiment, following the design of experiments methodology. The experiments were carried out with a complete 10 kW e SOFC system. Multivariate regression models are developed to estimate said temperature and a statistical analysis is carried out on the model parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…The experiment design used here extends that of the previous work [9], where it was found that while the three first inputs (I, _ V air and T air,in ) as such have a statistically significant effect on the stack temperature, their interactions do not. This enabled omitting the interaction effects of these inputs from the current experimental design.…”
Section: Experiments Designmentioning
confidence: 66%
See 4 more Smart Citations
“…The experiment design used here extends that of the previous work [9], where it was found that while the three first inputs (I, _ V air and T air,in ) as such have a statistically significant effect on the stack temperature, their interactions do not. This enabled omitting the interaction effects of these inputs from the current experimental design.…”
Section: Experiments Designmentioning
confidence: 66%
“…To meet these aims, the experiments were designed to fit within a pre-defined system operating space, and in particular, around two representative "central" operating conditions (Section 2). Thus, in comparison to the previous work [9,18], the data series collected and used in this study is larger in terms of the number of inputs as well as their range of variation. In addition, the number of data points collected is larger than before, which enables splitting the data set to a part used for model development and another part used solely for model validation.…”
Section: Background and Overview Of This Workmentioning
confidence: 95%
See 3 more Smart Citations